Perceived socially responsible-HRM on talent retention: The mediating effect of trust and motivation and the moderating effect of other-regarding value orientation - Rawshdeh, Zainab Ali; Makhbul, Zafir Khan Mohamed; Rawshdeh, Mustafa; Sinniah, Suguna (Frontiers in Psychology, 2023)
There is a growing interest concerning corporate social responsibility (CSR) and talent management, and the identified links between their aspects in literature. Thus, the current study examined the relationship between socially responsible Human Resource Management (SRHRM) -identified as CSR strategies and practices directed at employees to underpin the effectiveness of CSR implementation- and talent retention. In addition, this study employed a mediation-moderation framework with employee’s attitude (motivation and trust) as a mediating variable and other-regarding value orientation as a moderating variable. Thus, the current study will contribute to talent management and CSR current knowledge by analysing the depth of the relationship by way of exploring the moderating and mediating process. It answers the ‘how’ and ‘when’ questions and explains the mechanism through which an organisation can use its socially responsible HRM practices for retaining talented employees. The study sample comprised of 418 participants from Klang Valley area in Malaysia. The hypotheses in the study were tested using PLS structural equation modelling. The results of the study showed that (a) perceived SRHRM was positively related to talent retention; (b) this relationship was partially mediated by employee’s attitude (motivation and trust); and (c) other-regarding value orientation did not moderate the relationship between perceived SRHRM and talent retention. Furthermore, the study findings provide concrete and actionable recommendations on how to formulate and implement appropriate SRHRM policies and practices as they are not only essential for the successful implementation of external CSR programmes but also crucial to retain talented employees and improve their motivation and organisational trust.